Introducing 6G technology to support metaverse for telecommunication engineering students in Universitas Pendidikan Indonesia - Endah Setyowati; Syifaul Fuada; Khoirul Anwar; Muhamad Dzikri Danuarteu; Salwa Tasya Fathira Purba; Anggie Wijaya (Community Empowerment, 2023)
Research on 6G have been started with many applications including on the support of Metaverse, where humans can interact in cyberspace with real experiences. To introduce and provide an understanding of this technology, Program Studi Sistem Telekomunikasi Universitas Pendidikan Indonesia kampus Purwakarta held a Studium Generalle with the theme of "Knowing 6G Connectivity to Support the Metaverse" which was held in a hybrid manner. This Studium Generalle was filled by Assoc. Prof. Dr. Eng. Khoirul Anwar ST., M.Eng. (Director of The University Center of Excellence for Advanced Intelligent Communications or AICOMS and Lecturer of Tel-U). Participants were given a detailed description to contribute in the field of telecommunication research, such as 6G technology mainly on machine learning and quantum information processing. Participants have their understanding measured through Pre-Test and Post-Test. There are 8 multiple choices that are used as indicators of the success of knowledge transfer between the presenters and participants. Based on the answers of 174 participants who have taken the Post-Test, the percentage accuracy of participants's answers is 45%. With the majority of participants managed to answer 5 to 8 questions accurately. Overall, the public lecture is performed well as expected. Evaluation for the next activity is that students must first learn the basic understanding of the material to be delivered so that they can follow easily the lecture. Supporting devices are needed to improve audio quality for online participants and a wider venue for activities to accommodate more offline participants.